Attention to Woman in Abortion Situation at San José Hospital (2016-2019) [Atención a Mujeres en Situación de Aborto en el Hospital San José (2016-2019)] - Rubio-Schweizer, G (Sociedad Chilena de Obstetricia y Ginecologia, 2021)
Objective: To evaluate the incorporation of elements of quality of care for women in abortion situation (WAS) in the Sexual Health and Reproductive Health Unit of the San José Hospital, between 2016 and 2019 Methods: Using the data collected in the Perinatal Information System (SIP), a descriptive analysis of the sociodemographic characteristics was carried out and the implementation of the Sexual and Reproductive Health Unit was evaluated through quality care indicators. Results: The sociodemographic variables that characterize our population are defined by a high proportion of foreign women (44.5%), who have a medium educational level (63.8% secondary education and 26% university), and a high proportion of unmet needs for contraceptive methods (70.3%), representing sociodemographic characteristics similar to the different public health centers in the region. The trend of the quality of care indicators for women in abortion at the San José Hospital improved after the implementation of the Sexual and Reproductive Health Unit and the postabortion care model (PAC) by reducing non- recommended uterine evacuation methods. and increase coverage in immediate postabortion contraception. Conclusion: The implementation of a specialized unit in sexual and reproductive health improves the quality indicators of the WSA. © 2021 Sociedad Chilena de Obstetricia y Ginecologia. All rights reserved.